Evaluasi Tata Kelola dan Manajemen Risiko Teknologi Informasi pada PT. MyECO Teknologi Nusantara menggunakan Framework COBIT 2019 Proses EDM03 dan APO12 - Ayunda Della Ariesta; Suprapto Suprapto; Andi Reza Perdanakusuma (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2022)
PT. MyECO Teknologi Nusantara is a startup company that focuses on electricity-saving smarthome technology solutions. It has a product, namely an IoT-based automatic electricity-saving device. In supporting the quality of the company's products, MyECO has a smarthome application, namely the